STATINA touch interface-noise robustness problem - Chia, Lek Guan. (2013)
STATINA is a novel touch interface technology that is highly scalable to large sizes. However one of the in place is that is not robust against off-plane sound sources as such near-filed sources tend to turn up as false positives through the localisation algorithm at least around 50% of the time. Intuitively, such sources should propagate through air or some form of mixed mode propagation, hence should be localised outside of the plane interest. However, in this report, it has been found that such sources are often virtualised as sources on the plane, with an experimental propagation speed that is similar enough to that of the glass panel that it cannot be rejected naturally through localisation. Therefore it is recommended that other methods such as using peaks in the frequency spectrum should be explored to find possible means to reject such off-plane signals.